Batalhas virtuais pela memória : uma análise psicossocial da memória histórica do regime militar no Brasil - Flaviane da Costa Oliveira (2019)
This research focuses on the knowledge composition on the cyberculture. In order understand, from the Psychosocial Approach to Memory and Theory of Social Representations, the constructions of documental historical memory in the Brazilian military regime (1964-1985). This is a qualitative study which used the following sources for analysis; videos, transcriptions, public online commentaries which were available on YouTube-Br and the platform’s users responses to an online questionnaire. The website has approximately 850,000 videos on the theme, which demonstrates the users interest on this discussion. For this research, we selected videos with more than 200 thousand views or repeated among the first listed throughout the searches, totaling 35 videos. This work has three studies: 1. The content and the social mobilization of the videos and documents; 2. Discussions amongst the users in the commentary of the analyzed videos; 3. The social representations about the military regime for YouTube-Br users. The study 1 revealed a majority presence of productions that describe or name the period of military government as a "dictatorship" connecting past events to the present. The lexical analysis, using IRAMUTEQ® software, revealed two sets of word classes. On the one hand, the contents materialize structural and institutional aspects of the period (Classes 1 and 2); on the other hand, the contents present processes of categorization and disputes about social aspects, such as testimonies of those affected by the regime, imprisonment, repression, censorship and issues related to the guerrilla (Classes 3, 4 and 5). In study 2, the classes resulting from the lexical analysis of the comments were grouped into 21 main themes. These themes point to different aspects from the content of the videos when it describes the time as "good" and discuss the positive and negative sides of the period. The categories also encompass the definition of that time as "dictatorship" or "regime" and focus mainly on the possible "communist threat" that would find resonance in the current political context. Study 3 analyzed the results of the virtual questionnaire applied to 77 Internet users. The task of free evocation allowed the perception of the confrontation between two social groups, which were grouped accordingly to the political orientation. Thus, we hypothesized the presence of two poles of meaning. Pole 1, the political orientation mostly between the Centre and Left, it encompassed negative attitudes in relation to the period and had its central elements of the social representation of the regime by torture and dictatorship. Pole 2, with political orientation predominantly to the right or without orientation, associated positive attitudes to the military regime and indicated the possible central system of the representation formed by the elements: security, order, education, progress, respect, patriotism, and health. This research confirms that virtual spaces can become places of memory due to the mobilization of documents and the will of memory around the theme that foster the construction of knowledge. This connects past and present and helps us to understand social dynamics and contemporary policies. The presence of anti-communism and the identification of the regime as "good time" shows that the memory of the dictatorship is still under construction and warns us of the necessary protection of democracy.